EXCELLENT SERVICE STRATEGY AS AN EFFORT TO INCREASE BPJS PARTICIPANT SATISFACTION HEALTH RANTAUPRAPAT - Ariska, Nisa (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
Public satisfaction with public services in a country has been regulated in Law Number 25 of 2009 concerning Public Services Article 1 which reads Public Services are a series of activities in the context of fulfilling services in accordance with statutory regulations for every citizen and resident for goods, services and / or administrative services provided by public service providers. The purpose of this study was to determine the direct effect of excellent service on public satisfaction and company image, as well as the direct effect of public satisfaction on company image. Determination of the author's sample using the concept of Lameshow's theory so that in this study the people who are BPJS Health Rantauprapat participants from June-July 2024 so that in determining the sample of 100 people with data analysis using SmartPLS. The results of the study Excellent service has a direct effect on community satisfaction, this can be seen from the t-statistic value of 30.686 which is greater than the value of 1.96 with a significance level of 0.000 less than 0.05. Thus the results of testing the first hypothesis are accepted. Excellent service has no direct effect on institutional image, this can be seen from the t-statistic value of 1.508 which is smaller than the value of 1.96 with a significance level of 0.132 greater than 0.05. Thus the results of testing the first hypothesis are rejected. Community satisfaction has a direct effect on institutional image, this can be seen from the t-statistic value of 2.706 which is greater than the value of 1.96 with a significance level of 0.000 less than 0.05. Thus the results of testing the first hypothesis are accepted